Functional characterization of BrPHD58, an Alfin-like PHD finger protein from Brassica rapa, reveals its negative role in salt stress tolerance in Arabidopsis thaliana - Alam, Intikhab; Batool, Khadija; Ge, Hantao; Manghwar, Hakim; Rehman, Naveed Ur; Qiao, Fang; Wang, Hui-Cong (Frontiers in Plant Science, 2026)
The plant homeodomain (PHD) finger constitutes a subgroup of transcription factors that contribute to the coordination of plant growth, morphogenesis, and adaptation to environmental stress mechanisms. In this study, we identified and functionally characterized the BrPHD58 gene from Brassica rapa. Using sequence analysis, subcellular localization of BrPHD58–GFP fusion proteins, and transgenic Arabidopsis thaliana lines ectopically expressing BrPHD58, we investigated its role in salt stress responses, including seedling phenotypes and expression of salt-responsive genes. Subcellular localization analysis indicated that BrPHD58 predominantly accumulates within the nuclear compartment. Ectopic expression of BrPHD58 in A. thaliana significantly reduced seedling survival rates and root lengths under varying concentrations of NaCl compared to wild-type (WT) plants. Under soil-grown conditions, transgenic lines overexpressing BrPHD58 exhibited markedly decreased tolerance to salt stress. Moreover, ectopic expression of BrPHD58 led to a down regulation of key salt-responsive genes, AtRD22, AtRD29A, and AtLEA14, under salt stress conditions. Collectively, all these findings indicate that BrPHD58 acts as a negative modulator of salt stress tolerance in transgenic plants. Further investigation involving the development and analysis of BrPHD58 loss-of-function mutants in B. rapa is necessary to fully elucidate its physiological role in salinity adaptation.